Model Analisis Incident Management pada Layanan Teknologi Informasi Berdasarkan Framework Information Technology Infrastructure Library V3 - Maulana, Yoppy Mirza (Jurnal Saintekom : Sains, Teknologi, Komputer dan Manajemen, 2023)
Information Technology (IT) services are services developed by service provider organizations for customers. Service provider organizations in implementing IT services have a goal to ensure IT systems remain in good condition to avoid incidents. Incidents are unexpected interruptions and reductions in the quality of IT services. Therefore, when an incident occurs in IT services, it is necessary to recover as quickly as possible or it is called incident management. Incident management is very important for service provider organizations, because if incidents are not managed and analyzed carefully then these incidents will recur. On this basis, a study was conducted to develop an IT service incident management analysis model based on the Information Technology Infrastructure Library (ITIL) V3 which aims to serve as a guide in analyzing and making recommendations for incident management. This model uses case studies in the PPTI section at Dinamika University. This model produces three stages including the incident data collection stage which produces IT service incident data. The incident management analysis stage produces a gap analysis, while the recommendation stage produces recommendations for improvement.